2018
DOI: 10.5935/abc.20180167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardiac and Vascular Parameters in Powerlifters and Long-Distance Runners: Comparative Cross-Sectional Study

Abstract: BackgroundCardiac remodeling is a specific response to exercise training and time exposure. We hypothesized that athletes engaging for long periods in high-intensity strength training show heart and/or vascular damage.ObjectiveTo compare cardiac characteristics (structure and function) and vascular function (flow-mediated dilation [FMD] and peripheral vascular resistance [PVR]) in powerlifters and long-distance runners.MethodsWe evaluated 40 high-performance athletes (powerlifters [PG], n = 16; runners [RG], n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Resting blood pressure ≥ 130/80 mmHg (previously ≥ 140/90 mmHg) is defined as hypertension [ 25 ] and is considered a risk factor for stroke, heart attack, kidney failure and congestive heart failure [ 26 ]. In a group of natural powerlifters, it was shown that resting blood pressure was significantly higher compared to a group of endurance runners (130/82 mmHg versus 116/72 mmHg, respectively) [ 27 ]. In the present study, the resting blood pressure of the participants was considered healthy since the readings were less than 120/80 mmHg [ 25 ] and did not change between training phases.…”
Section: Discussionmentioning
confidence: 99%
“…Resting blood pressure ≥ 130/80 mmHg (previously ≥ 140/90 mmHg) is defined as hypertension [ 25 ] and is considered a risk factor for stroke, heart attack, kidney failure and congestive heart failure [ 26 ]. In a group of natural powerlifters, it was shown that resting blood pressure was significantly higher compared to a group of endurance runners (130/82 mmHg versus 116/72 mmHg, respectively) [ 27 ]. In the present study, the resting blood pressure of the participants was considered healthy since the readings were less than 120/80 mmHg [ 25 ] and did not change between training phases.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been increased interest in understanding the cardiac response to different types of resistance training in male athletes. [3][4][5][6]20 The cardiac adaptations to resistance training involve geometrical re-orientation in different patterns including concentric remodeling, concentric hypertrophy, or eccentric hypertrophy. 3,12 Our findings suggest resistance-trained female athletes may experience heterogeneous LV geometries, including mostly concentric hypertrophy, eccentric hypertrophy, or normal patterns (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Resistance training is an effective method of conditioning to enhance muscle strength (ie, ability to generate muscle force), while also promoting other health-related benefits including increased bone mass and muscle cross-sectional area, as well as decreased body fat and blood pressure in females. 1,3 As such, re- Increased interest has emerged in quantifying cardiac morphology and function in resistance-trained male athletes [3][4][5][6] to understand specific adaptations and potential negative responses to resistance training protocols. For instance, a review by Haykowsky et al 3 revealed intense dynamic and isometric resistance training increases concentric left ventricular (LV) hypertrophy, which is characterized by an increase in LV mass with an augmented ratio of wall thickness to LV diameter.…”
Section: Introductionmentioning
confidence: 99%
“…To differentiate normal adaptive responses ("benign") from abnormal ones remains a challenge. Here we address some important issues related to the discussion on cardiac remodeling in exercise, recently revisited by Vidaletti-Silva and colleagues 1 in this issue.…”
mentioning
confidence: 99%
“…Although well-established in scientific literature, Vidaletti-Silva et al 1 have addressed the question of differences in cardiac remodeling due to sports modalities through a cross-sectional, comparator-group design, comparing endurance athletes (i.e., runners) and strength-trained athletes (i.e., powerlifters) - two classes and levels of modalities that seem appropriate for this comparison. In their findings, no moment-differences between groups were observed for the LV mass, when adjusted for their surface area.…”
mentioning
confidence: 99%